Pemeriksaan Antibody Dengue Pada Darah Donor di PMI Kabupaten Sleman Dengan Metode Rapid Test - Serafica Btari Chrisityani Kusumaningrum; Wiwit Sepvianti (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Dengue Hemorrhagic Fever (DHF) is a disease caused by Dengue Virus (DENV), which concluding serotypes (1-4) through mosquito bites and transmitted into humans. DHF is endemic and has increasing cases every year in almost every region in Indonesia, such as Kabupaten Sleman. Currently, screening for Infectious Diseases Transmitted by Blood Transfusion in blood donor only requires Hepatitis B, Hepatitis C, HIV, and Syphilis, despite any other diseases such as Dengue. Therefore, this study needs to detect the IgG/IgM Dengue antibodies on blood donor obtained from PMI Sleman to ensure safety and good quality of blood donor. This research method is used descriptive observational research and the samples are obtained from PMI Sleman. Examining for Dengue IgG/IgM antibodies for donor blood samples was accomplished by the rapid test method. The results showed that all blood donor samples were non-reactive from Hepatitis B, Hepatitis C, HIV, and Syphilis as Infectious Diseases Transmitted by Blood Transfusion. There were 16 (51,72%) blood samples that were reactive of IgG/IgM Dengue and 13 (44,83%) blood samples were non-reactive IgG/IgM Dengue. The reactive blood samples divide into four blood groups, there were 7 (24,14%) samples of blood type A,Rh+; 1 (3,45%) sample of blood type B, Rh+; 2 (6,90%) samples with blood type B,Rh+; 2 (6,90%) samples with blood type AB,Rh+ and 6 (20,69%) samples with blood type of AB, Rh+. Moreover, the reactive donor blood samples divide as 15 (24,14%) samples were in the 17-30 years-old age group and there was 1 (3,45%) was from the 31-40 years-old age group.